Analysis of The Influence of Education, Health, and Internet User on Economic Growth With Labor Productivity as an Intervening Variable in Indonesia - Simatupang, Dewi Ratna Sari; Yola Anggia; Raina Linda Sari; Inggrita Gusti Sari Nasution, (Journal Of Management Analytical and Solution (JoMAS), 2023)
This study aims to see whether the Labor Productivity variable is able to become an intervening variable between the Education, Health and Internet Users variable on Indonesia's Economic Growth in the 2015- 2019 period. The method used is Path Analysis using the Eviews program. The data used is in the form of panels consisting of 34 provinces in Indonesia over a period of 5 (five) years. For model selection using the Chow Test and Hausman Test and from the two tests the Fixed Effect Model was selected. For the value of the Education Variable, the average length of school data is used; the health variable uses life expectancy data and vaternet uses internet user data. The results of this study indicate that the Labor Productivity variable is not an intervening variable between the Education, Health, Internet variable and the Economic Growth variable as seen from the Sobel Test results which have a value of less than 1.96 at ð›¼=5%. The direct effect of the Education variable on Labor Productivity is negative and not significant. The direct effect of the Health variable on Labor Productivity is negative and significant. The direct effect of the Internet variable on Labor Productivity is positive and not significant. The direct effect of the Education variable on Economic Growth is negative and significant. The direct effect of the Health variable on Economic Growth is positive and not significant. The direct effect of Internet variable on economic growth is positive and significant. The direct effect of the Labor Productivity variable on Economic Growth is negative and not significant.